Design of wide band underwater antenna using buffer layer structure for underwater communication / Hanisah Mohd Zali - Mohd Zali, Hanisah (2023)
Utilization of electromagnetic wave (EMW) in underwater wireless communication systems is being investigated as the alternative to the conventional acoustic-based system, in order to provide higher data rate. However, underwater EMW systems has the drawback of the high signal attenuation, effecting the signal quality and data rate. In underwater environment, conventional antennas will perform poorly since they have reduced efficiency and poor near-field radiation properties. Hence, a proper optimized antenna design is required to enhance the antenna performances underwater. Existing works on the development of the underwater antennas mostly focus on the development on narrowband antennas operating at low frequencies. Moreover, most studies on EMW propagation in underwater investigate only the propagation of narrowband signal. While utilization of wider signal bandwidth permits a higher data rate, there are minimal study to investigate the wideband antenna design and propagation characteristics. The main aim of this study is to develop a wideband patch antenna, integrated with buffer layer configuration for enhanced underwater transmission. Accordingly, the present study investigates the parameters of a buffer layer in enhancing the proposed wideband underwater antenna performance, with experimental validation. For the buffer layer, this study proposes the utilization of a material with relative permittivity between the atmosphere and water, to enhance the antenna performance. Furthermore, the present study also analyses the wideband electromagnetic wave path loss in the underwater environment through measurement and validation with numerical evaluation.